2006
DOI: 10.1128/mcb.00856-06
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Incorporation of Multiple Selenocysteines Involves an Inefficient Decoding Step Serving as a Potential Translational Checkpoint and RibosomeBottleneck

Abstract: Selenocysteine is incorporated into proteins via "recoding" of UGA from a stop codon to a sense codon, a process that requires specific secondary structures in the 3 untranslated region, termed selenocysteine incorporation sequence (SECIS) elements, and the protein factors that they recruit. Whereas most selenoprotein mRNAs contain a single UGA codon and a single SECIS element, selenoprotein P genes encode multiple UGAs and two SECIS elements. We have identified evolutionary adaptations in selenoprotein P gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
58
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 27 publications
11
58
1
Order By: Relevance
“…We found SECIS 1 to be a dominant regulator of Sec incorporation with SECIS 2 seeming largely dispensable. Overall, these results are congruous with the finding from zebrafish Sel P where mutating SECIS 1 was more detrimental to Sec incorporation than mutating SECIS 2 but the latter was required for processive Sec incorporation (13).…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…We found SECIS 1 to be a dominant regulator of Sec incorporation with SECIS 2 seeming largely dispensable. Overall, these results are congruous with the finding from zebrafish Sel P where mutating SECIS 1 was more detrimental to Sec incorporation than mutating SECIS 2 but the latter was required for processive Sec incorporation (13).…”
Section: Discussioncontrasting
confidence: 45%
“…The role of the dual SECIS elements has only recently been studied in detail. In 2006 Stoytcheva et al (13) determined that the second SECIS element of zebrafish Sel P was required for readthrough of the first UGA and the first SECIS element was necessary for readthrough of subsequent UGAs and consequently, production of full-length protein (13). However, the mechanistic basis for this distinction of function remains elusive.…”
mentioning
confidence: 99%
“…While most, if not all, of the numerous molecular actors involved have been identified ), the mechanistic issues are still shrouded in mystery. The question is even more acute when considering the case of the selenoprotein P mRNA, which contains 10-17 UGA Sec codons and two SECIS elements (Stoytcheva et al 2006). In an attempt to increase our knowledge, in the work described here, we designed for the first time a minimal capped selenoprotein mRNA bearing photoreactive groups in the SECIS element.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the intriguing question of how the translation machinery decides between termination and translation at these UGA sites. A potential model was recently presented, suggesting that the two SECIS elements play different roles in the synthesis of SelP (292). It appears that SECIS 1 promotes the readthrough of the second and subsequent UGA codons directing synthesis of fulllength SelP, whereas SECIS 2 plays a more substantial role in decoding the first UGA codon, potentially controlling translation of the truncated isoforms.…”
Section: From Selenium To Selenoproteins 779mentioning
confidence: 99%
“…It appears that SECIS 1 promotes the readthrough of the second and subsequent UGA codons directing synthesis of fulllength SelP, whereas SECIS 2 plays a more substantial role in decoding the first UGA codon, potentially controlling translation of the truncated isoforms. Hence, the interplay between the SECIS elements and distinct UGA codons could serve both as a translational checkpoint to determine the fate of the mRNA, depending on intracellular selenium status, and a bottleneck for ribosome loading on the mRNA to decode multiple UGA codons (292 (150,191). One of the studies found that cancer carriers were twice as frequently homozygotes for the A than the G allele (150).…”
Section: From Selenium To Selenoproteins 779mentioning
confidence: 99%